DISCRETE FRACTIONAL SOLUTIONS OF A HERMITE EQUATION - Yilmazer, Resat (Univ Prishtines, 2019)
Discrete fractional calculus has an important role in fractional analysis. In this article, we obtain new fractional solutions of the second order homogeneous and nonhomogeneous Hermite differential equation by using discrete fractional nabla operator. In addition, explicit solutions for the partial differential equation that can be converted to the Hermite equation have been obtained.
Keywords: Discrete fractional calculus; Leibniz rule; Nabla operator